Silicon-doped nickel-manganese-based layered oxide positive electrode material and preparation method and application thereof
By doping silicon in the nickel-manganese base layered oxide positive electrode material to form Si-O bonds at tetrahedral positions, the reversibility of anion redox reaction and the Jahn-Teller distortion problems of Mn3+ are solved, and the cyclic stability and specific capacity of the material are significantly improved, and stable output with high energy density is achieved.
Patent Information
- Application Number
- CN202510166486.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-12-12
- Filing Date
- 2025-02-14
- Publication Date
- 2025-05-30
AI Technical Summary
In the nickel-manganese base layered oxide sodium storage cathode, it is difficult to achieve a highly reversible anionic redox reaction at the same time, and the Jahn-Teller distortion of Mn3+ is alleviated without losing the Mn redox capacity, ensuring the stable output of the high energy density of the material.
SizO2 is prepared by the sol-gel method for preparing the Si-doped nickel-manganese base layered oxide positive electrode material. The doped element Si is located in the tetrahedral position and forms a strong covalent bond with O, stabilizes the anionic redox reaction, and reduces the valence state of Mn through the incorporation of Si, and alleviates Jahn-Teller distortion.
It significantly improves the reversibility of the anion and cationic reaction of the material, improves the cycle stability and specific capacity, and improves the rate performance, achieving stable output with high energy density.
Smart Images

Figure CN120072925A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium-ion batteries, and particularly relates to a silicon-doped nickel manganese-based layered oxide cathode material, a preparation method thereof, and an application thereof. Background Art
[0002] With the increasing depletion of traditional fossil energy, renewable clean energies (such as solar energy, wind energy, tidal energy, etc.) have attracted wide attention from people, and it is imperative to develop large-scale energy storage devices. Compared with lithium-ion batteries, sodium-ion batteries have rich resources and low prices, and are considered to be one of the secondary batteries most promising for application in large-scale energy storage systems. The cathode material of sodium-ion batteries determines the cost and performance of the battery. Therefore, the development of cathode materials with high specific energy, high rate performance, and long life is the current research focus. Among them, layered transition metal oxides have received extensive attention due to their high theoretical capacity, suitable working voltage, environmental friendliness, and compositional tunability.
[0003] Compared with traditional layered oxide cathode materials with only cationic redox reactions, lithium nickel manganese-based oxides can also provide additional capacity generated by anionic redox reactions, and have lower costs, which are very suitable for large-scale energy storage. However, at high voltages, some O 2- is likely to form O 2 and release during the oxidation process, resulting in structural damage and capacity decay. In addition, the Jahn-Teller effect of Mn 3+ at low voltages will cause structural distortion, affecting the cycle stability.
[0004] To address the above problems, some effective modification strategies have been successively proposed. For example, Prof. Haoshen Zhou et al. doped Ir element to form strong covalent bonds with O, stabilized the anion redox reaction, and inhibited the lattice oxygen overflow (H. Zhou, X. Zhang, Y. Qiao, et al. Manganese-Based Na-Rich Materials Boost Anionic Redox in High-Performance Layered Cathodes for Sodium-Ion Batteries. Adv. Mater. 2019, 31, 1807770.); Prof. Yongchang Liu et al. doped Ca element at the Na ion site to form Ca-O bonds with higher bond energy than Na-O bonds, stabilizing the anion redox reaction (Q. Shen, Y. Liu, X. Zhao, et al. Transition-Metal Vacancy Manufacturing and Sodium-Site Doping Enable a High-Performance Layered Oxide Cathode through Cationic and Anionic Redox Chemistry. Adv. Funct. Mater. 2021, 31, 2106923); Prof. Yong Yang et al. doped Al element to reduce the formation of the Jahn-Teller center of Mn 3+ and improve the cycle stability of the material (Y. Yang, X. Liu, W. Zuo, et al. P2-Na 0.67 Al x Mn 1−x O 2 : Cost-Effective, Stable and High-Rate Sodium Electrodes by Suppressing Phase Transitions and Enhancing Sodium Cation Mobility, Angew. Chem. Int. Ed. 2019, 58, 18086.).
[0005] However, it is still a great challenge to simultaneously achieve a highly reversible anion redox reaction in the nickel-manganese-based layered oxide sodium storage cathode and alleviate the Jahn-Teller distortion of Mn without losing the Mn redox capacity to ensure the stable output of high energy density of the material. 3+ Summary of the Invention
[0006] Based on the above background, the present invention provides a silicon-doped nickel-manganese-based layered oxide cathode material for sodium-ion batteries, its preparation method and application. By the sol-gel method, a nickel source, a manganese source, a lithium source, a sodium source are weighed according to the corresponding stoichiometric ratios and an appropriate amount of silicon element is introduced. After continuous stirring and evaporation of the solvent, a wet gel is formed. It is dried and ground into powder, and a silicon-doped nickel-manganese-based oxide cathode material Na x Li 0.1 Ni y Mn (1-0.1-y) Si z O 2 is obtained through stepwise calcination in an air atmosphere; wherein, 0.55 ≤ x ≤ 0.85, 0.1 ≤ y ≤ 0.4, 0 < z < 0.1. The doped element Si is located in the tetrahedral position and forms strong covalent bonds with O, which can stabilize the anion redox reaction. At the same time, after Si is incorporated, the valence state of Mn decreases, and the Mn 3+ / Mn 4+ redox couple can contribute more capacity, significantly improving the material capacity. In addition, the pinning effect of Si atoms in the tetrahedral position can alleviate the Jahn-Teller distortion of Mn 3+ , significantly improving the cycle stability of the material. Finally, Si is located in the tetrahedral position, and its repulsive force with Na e site Na + increases the O-Na-O spacing, improving the diffusion ability of Na + , effectively improving the rate performance of the material. Therefore, doping Si element into the nickel-manganese-based layered oxide cathode can significantly improve the reversibility of the cation and anion reactions of the material, thereby improving the cycle stability of the material, and at the same time can improve its specific capacity and rate performance.
[0007] Based on the above object, the present invention adopts the following technical solutions:
[0008] The present invention provides a silicon-doped nickel-manganese-based layered oxide cathode material, whose chemical formula is Na x Li 0.1 Ni y Mn (1-0.1-y) Si z O 2 ; wherein, 0.55 ≤ x ≤ 0.85, 0.1 ≤ y ≤ 0.4, 0 < z < 0.1.
[0009] The present invention also provides a preparation method of the silicon-doped nickel-manganese-based layered oxide cathode material, including the following steps:
[0010] 1) Prepare an aqueous citric acid solution, where citric acid serves as a complexing agent; add a lithium source, a nickel source of transition metal elements, a manganese source, and a silicon source of doping elements according to the corresponding stoichiometric ratios, then add a sodium source, and stir to form a homogeneous solution;
[0011] 2) Heat and stir the solution described in step 1) under a water bath condition until a wet gel is formed. Subsequently, place the gel in an oven to dry until all the water is removed, and then grind the obtained solid into powder;
[0012] 3) Place the powder described in step 2) in a muffle furnace and conduct a first high-temperature calcination to obtain an intermediate product, and grind it into powder;
[0013] 4) Place the powder described in step 3) in a muffle furnace and conduct a second high-temperature calcination to obtain a P2-phase doped and modified cathode material Na x Li 0.1 Ni y Mn (1-0.1-y) Si z O 2 。
[0014] Further, in step 1), the stoichiometric ratio of citric acid to transition metal salts is between 1.5:1 and 2.5:1, and the transition metal salts are nickel salts and manganese salts; the addition amounts of the lithium source and the sodium source are 3 - 6% in excess molar ratio to compensate for the loss of lithium and sodium during calcination; the sodium source is any one of sodium acetate, sodium nitrate, sodium carbonate, and sodium bicarbonate; the lithium source is any one of lithium acetate, lithium nitrate, and lithium sulfate; the nickel source is any one of nickel acetate, nickel nitrate, and nickel sulfate; the manganese source is any one of manganese acetate, manganese nitrate, and manganese sulfate; the silicon source is tetraethyl orthosilicate.
[0015] Further, in step 2), the water bath temperature is 70 - 90 °C; the drying temperature is 105 - 125 °C, and the drying time is 5 - 10 h.
[0016] Further, in step 3), the first calcination temperature is 350 - 550 °C, the heating rate is 4 - 6 °C min -1 , the calcination time is 4 - 6 h, and then it is cooled naturally. At this calcination temperature, the citric acid and acetate radicals in the material are converted into water and carbon dioxide, thereby removing carbon and hydrogen to obtain an intermediate product.
[0017] Further, in step 4), the second calcination temperature is 750 - 950 °C, the heating rate is 4 - 6 °C min -1 , the calcination time is 10 - 15 h, and then it is cooled at 4 - 6 °C min -1 to 400 °C and then cooled naturally. The second calcination is carried out at this temperature to further crystallize the disordered phase obtained from the first calcination, and obtain a P2-phase doped and modified cathode material.
[0018] The present invention also provides the application of the silicon-doped nickel manganese layered oxide cathode material, including mixing Na x Li 0.1 Ni y Mn (1-0.1-y) Si z O 2 powder, acetylene black and binder polyvinylidene fluoride (PVdF) in a mass ratio of 70:20:10, grinding them evenly and then coating them on an aluminum foil current collector, and drying them in a vacuum drying oven to make a positive electrode sheet for a sodium-ion battery.
[0019] Further, the positive electrode sheet made by mixing Na x Li 0.1 Ni y Mn (1-0.1-y) Si z O 2 powder, acetylene black and binder polyvinylidene fluoride (PVdF) is used as the positive electrode of a sodium-ion battery. Using metallic sodium as the counter electrode, 5 vol% fluoroethylene carbonate (FEC) is added to 1 mol / L sodium perchlorate 4 / propylene carbonate (PC) as the electrolyte, and glass fiber as the separator, and assembling it into a CR2032 button battery in a high-purity argon gas atmosphere glove box with water and oxygen contents both less than 0.01 ppm.
[0020] Compared with the prior art, the advantages of the present invention are:
[0021] The material preparation process is simple and easy to operate, the conditions are controllable, the repeatability is good, and the doping modification effect is obvious. The doping element silicon is located in the tetrahedral position and can form strong covalent bonds with O, thus stabilizing the anion redox reaction. At the same time, after Si is incorporated, the valence state of Mn decreases, and the Mn 3+ / Mn 4+ redox couple can contribute more capacity, significantly improving the material capacity. In addition, the pinning effect of Si atoms in the tetrahedral position can relieve the Jahn-Teller distortion of Mn 3+ , significantly improving the cycle stability of the material. Finally, Si is located in the tetrahedral position, and its repulsive force with Na e site Na + increases the O-Na-O spacing, improving the diffusion ability of Na + , effectively improving the rate performance of the material. At the same time, the role of Li is to activate the anion redox reaction in the material, and the role of Ni is to increase the specific capacity of the material. Therefore, Na x Li 0.1 Ni y Mn (1-0.1-y) Si z O2 When used as a cathode material for sodium-ion batteries, it can simultaneously achieve high specific energy and long cycle life, showing good prospects for practical applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] To more clearly illustrate the technical solutions in the embodiments of the present invention, the following will briefly introduce the drawings required for the description of the embodiments. Obviously, the drawings in the following description are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can be obtained based on these drawings.
[0023] Figure 1 XRD patterns of the cathode materials of Examples 1, 2, and 3 of the present invention 0.82 Li 0.1 Ni 0.24 Mn 0.66 Si 0.03 O 2 、Na 0.82 Li 0.1 Ni 0.24 Mn 0.66 Si 0.02 O 2 、Na 0.82 Li 0.1 Ni 0.24 Mn 0.66 Si 0.04 O 2 XRD patterns of the cathode materials;
[0024] Figure 2 SEM, TEM, and EDS mapping diagrams of the cathode material prepared in Example 1 of the present invention 0.82 Li 0.1 Ni 0.24 Mn 0.66 Si 0.03 O 2 SEM, TEM, and EDS mapping diagrams of the cathode material;
[0025] Figure 3 Charge-discharge curves of the button battery assembled with the cathode material prepared in Example 1 of the present invention and its comparison with 0.82 Li 0.1 Ni 0.24 Mn 0.66 Si 0.03 O 2 Charge-discharge curves of the button battery assembled with the cathode material and its comparison with 0.82 Li 0.1 Ni 0.24 Mn 0.66 Si 0.02 O 2 、Na 0.82 Li 0.1 Ni0.24 Mn 0.66 Si 0.04 O 2 , and Na without doped Si 0.82 Li 0.1 Ni 0.24 Mn 0.66 O 2 Comparison chart of cycle performance. Specific implementation mode
[0026] To make the technical problems, technical solutions and advantages to be solved by the present invention clearer, the following will be described in detail with reference to the drawings and specific embodiments.
[0027] Example 1
[0028] 1) Take 60 mL of deionized water, add 10 mmol of anhydrous citric acid, and stir until completely dissolved; then take 4.305 mmol of anhydrous sodium acetate, 0.515 mmol of anhydrous lithium acetate, 3.3 mmol of manganese acetate tetrahydrate, 1.2 mmol of anhydrous nickel acetate, and 0.15 mmol of tetraethyl orthosilicate and add them to the above solution in sequence, and continuously stir for 1 h until a homogeneous solution is formed;
[0029] 2) Stir the above solution in a water bath at 80 °C for 3 h to evaporate the water and form a wet gel. Then place the gel in an oven and dry it at 110 °C for 6 h to completely remove the water, and grind it into powder;
[0030] 3) Place the above powder in a muffle furnace and heat it to 450 °C at a heating rate of 5 °C / min -1 and calcine for 5 h to obtain an intermediate product, and grind it into powder;
[0031] 4) Place the above powder in a muffle furnace and heat it to 900 °C at a heating rate of 5 °C / min -1 and calcine for 12 h to obtain the cathode material Na 0.82 Li 0.1 Ni 0.24 Mn 0.66 Si 0.03 O 2 .
[0032] Use the Na 0.82 Li 0.1 Ni 0.24 Mn 0.66 Si 0.03 O 2 cathode material prepared in Example 1 to make an electrode according to the following method:
[0033] Put Na 0.82 Li 0.1 Ni 0.24 Mn 0.66Si 0.03 O 2 The positive electrode material, acetylene black, and the binder polyvinylidene fluoride (PVdF) are mixed in a mass ratio of 70:20:10, ground evenly, coated on an aluminum foil current collector, and dried to make a positive electrode sheet for a sodium-ion battery. Using metallic sodium as the counter electrode, a solution of 1 mol / L NaClO 4 / PC with 5 vol% fluoroethylene carbonate (FEC) is used as the electrolyte, and glass fiber is used as the separator. A CR2032 button battery is assembled in a high-purity argon glove box with water and oxygen contents both less than 0.01 ppm.
[0034] Figure 1 are the Na in Examples 1, 2, and 3 of the present invention 0.82 Li 0.1 Ni 0.24 Mn 0.66 Si 0.03 O 2 、Na 0.82 Li 0.1 Ni 0.24 Mn 0.66 Si 0.02 O 2 、Na 0.82 Li 0.1 Ni 0.24 Mn 0.66 Si 0.04 O 2 XRD patterns of the positive electrode materials. By comparing with the standard diffraction cards, it is found that the prepared materials are all in the hexagonal structure P2 phase, and the diffraction peaks are sharp, indicating that the material purity and crystallinity are relatively high. According to the different sodium ion coordination environments, layered oxide positive electrode materials can be divided into P-type and O-type, where P and O represent that sodium ions occupy the prismatic position and the octahedral position respectively. According to the different stacking orders of oxygen layers, they can be further divided into types such as P2, P3, and O3, and the numbers represent the stacking layers of oxygen layers in the minimum repeating unit. Due to the structural differences, there are significant differences in their electrochemical properties. P2-type materials have wider sodium ion transport channels and lower sodium ion migration energy barriers, showing faster diffusion kinetics, but lower initial capacity, and are prone to P2→O2 phase transformation, which affects the cycle stability.
[0035] Figure 2 is the Na prepared in Example 1 of the present invention 0.82 Li 0.1 Ni 0.24 Mn 0.66 Si 0.03 O 2SEM, TEM, and EDS mapping images of the positive electrode material. Figure a shows Na in Example 1 of the present invention 0.82 Li 0.1 Ni 0.24 Mn 0.66 Si 0.03 O 2 SEM image of the positive electrode material shows that the material morphology is uniformly distributed flaky particles with a size of 2.5 - 4.0 μm. Figures b and c are TEM images of the material, and the clear and regular lattice fringes confirm that the material has a well-crystallized layered structure with an interlayer spacing of 0.57 nm. Figure d is the EDS mapping image of the material, and it can be seen that the elements Na, Mn, Ni, O, and Si are uniformly distributed.
[0036] Figure 3 is the Na prepared in Example 1 of the present invention 0.82 Li 0.1 Ni 0.24 Mn 0.66 Si 0.03 O 2 Charge-discharge curves of the button battery assembled with the positive electrode material and its comparison with Na 0.82 Li 0.1 Ni 0.24 Mn 0.66 Si 0.02 O 2 , Na 0.82 Li 0.1 Ni 0.24 Mn 0.66 Si 0.04 O 2 , and the cycle performance comparison diagram of Na without Si doping 0.82 Li 0.1 Ni 0.24 Mn 0.66 O 2 Figure a shows the charge-discharge curve of the button battery assembled with the Na 0.82 Li 0.1 Ni 0.24 Mn 0.66 Si 0.03 O 2 positive electrode material of the present invention. In the voltage range of 1.7 - 4.3 V and at a current density of 0.1 C, the first-cycle discharge capacity is as high as 192 mAh g -1 . Figure b shows that Na 0.82 Li 0.1 Ni 0.24 Mn 0.66 Si 0.03 O 2 After 50 cycles at 0.1 C, its capacity retention rate can reach 93.7%. Compared with Na in Comparative Example 10.82 Li 0.1 Ni 0.24 Mn 0.66 O 2 (The capacity retention rate after 50 charge-discharge cycles is 78.5%). Na in Example 2 0.82 Li 0.1 Ni 0.24 Mn 0.66 Si 0.02 O 2 (The capacity retention rate after 50 charge-discharge cycles is 83.2%). Na in Example 3 0.82 Li 0.1 Ni 0.24 Mn 0.66 Si 0.04 O 2 (The capacity retention rate after 50 charge-discharge cycles is 87.2%). The cycle stability is significantly improved compared with
[0037] Example 2
[0038] 1) Take 60 mL of deionized water, add 10 mmol of anhydrous citric acid, and stir until completely dissolved; then take 4.305 mmol of anhydrous sodium acetate, 0.515 mmol of anhydrous lithium acetate, 3.3 mmol of manganese acetate tetrahydrate, 1.2 mmol of anhydrous nickel acetate, and 0.1 mmol of tetraethyl orthosilicate and add them to the above solution in sequence, and continuously stir for 1 h until a homogeneous solution is formed;
[0039] 2) Stir the above solution in a water bath at 80 °C for 3 h to evaporate the water and form a wet gel. Then place the gel in an oven and dry it at 110 °C for 6 h to completely remove the water, and grind it into powder;
[0040] 3) Place the above powder in a muffle furnace and heat it to 450 °C at a heating rate of 5 °C min -1 and calcine it for 5 h to obtain an intermediate product, and grind it into powder;
[0041] 4) Place the above powder in a muffle furnace and heat it to 900 °C at a heating rate of 5 °C min -1 to obtain the cathode material Na 0.82 Li 0.1 Ni 0.24 Mn 0.66 Si 0.02 O 2 .
[0042] Assemble the cathode material prepared in Example 2 into a CR2032 button battery according to the method in Example 1. At a current density of 0.1C, its initial discharge capacity is 179.2 mAh g -1After 50 cycles, the capacity retention rate is 83.2%, relatively improving the specific capacity and cycle stability of the Ni-Mn-based layered oxide material.
[0043] Example 3
[0044] 1) Take 60 mL of deionized water, add 10 mmol of anhydrous citric acid, and stir until completely dissolved; then take 4.305 mmol of anhydrous sodium acetate, 0.515 mmol of anhydrous lithium acetate, 3.3 mmol of manganese acetate tetrahydrate, 1.2 mmol of anhydrous nickel acetate, and 0.2 mmol of tetraethyl orthosilicate and add them to the above solution in sequence, and continuously stir for 1 h until a homogeneous solution is formed;
[0045] 2) Stir the above solution in a water bath at 80 °C for 3 h to evaporate the water and form a wet gel. Then place the gel in an oven and dry it at 110 °C for 6 h to completely remove the water, and grind it into a powder;
[0046] 3) Place the above powder in a muffle furnace and heat it at a heating rate of 5 °C / min -1 to 450 °C and calcine for 5 h to obtain an intermediate product, and grind it into a powder;
[0047] 4) Place the above powder in a muffle furnace and heat it at a heating rate of 5 °C / min -1 to 900 °C and calcine for 12 h to obtain the positive electrode material Na 0.82 Li 0.1 Ni 0.24 Mn 0.66 Si 0.04 O 2 .
[0048] Assemble the positive electrode material prepared in Example 3 into a CR2032 button battery according to the method in Example 1. At a current density of 0.1C, its initial discharge capacity is 183.7 mAh g -1 , and after 50 cycles, the capacity retention rate is 87.2%, relatively improving the specific capacity and cycle stability of the Ni-Mn-based layered oxide material.
[0049] Example 4
[0050] 1) Take 60 mL of deionized water, add 10 mmol of anhydrous citric acid, and stir until completely dissolved; then take 4.305 mmol of anhydrous sodium acetate, 0.515 mmol of anhydrous lithium acetate, 3.3 mmol of manganese acetate tetrahydrate, 1.2 mmol of anhydrous nickel acetate, and 0.4 mmol of tetraethyl orthosilicate and add them to the above solution in sequence, and continuously stir for 1 h until a homogeneous solution is formed;
[0051] 2) Stir the above solution in a water bath at 80 °C for 3 h to evaporate the water and form a wet gel. Then, place the gel in an oven and dry it at 110 °C for 6 h to completely remove the water, and grind it into powder;
[0052] 3) Place the above powder in a muffle furnace and heat it at a heating rate of 5 °C / min -1 to 450 °C and calcine for 5 h to obtain an intermediate product, and grind it into powder;
[0053] 4) Place the above powder in a muffle furnace and heat it at a heating rate of 5 °C / min -1 to 900 °C and calcine for 12 h to obtain the cathode material Na 0.82 Li 0.1 Ni 0.24 Mn 0.66 Si 0.08 O 2 。
[0054] Assemble the cathode material prepared in Example 4 into a CR2032 button battery according to the method in Example 1. At a current density of 0.1C, its initial discharge capacity is 168.7 mAh g -1 , and after 50 cycles, the capacity retention rate is 80.5%, which relatively improves the specific capacity and cycle stability of the Ni-Mn-based layered oxide material.
[0055] As can be seen from Examples 1-4, as the Si doping amount increases, the specific capacity of the material first increases and then decreases. This is because when the Si doping amount is low, the valence state of Mn is relatively high, and the capacity contributed by the Mn 3+ / Mn 4+ redox couple is relatively low; when the Si doping amount is high, the capacity contributed by the anion redox reaction is relatively low. In addition, as the Si doping amount increases, the cycle stability of the battery first increases and then decreases. This is because when the Si doping amount is low, the anion redox reaction contributes more capacity, but due to the small Si doping amount, the oxygen loss during the reaction cannot be well inhibited. When the Si doping amount is high, the valence state of Mn is relatively low, and the Jahn-Teller distortion of Mn 3+ is severe, resulting in poor cycle stability.
[0056] Comparative Example 1
[0057] 1) Take 60 mL of deionized water, add 10 mmol of anhydrous citric acid, and stir until completely dissolved; then take 4.305 mmol of anhydrous sodium acetate, 0.515 mmol of anhydrous lithium acetate, 3.3 mmol of manganese acetate tetrahydrate, and 1.2 mmol of anhydrous nickel acetate and add them to the above solution in sequence, and continuously stir for 1 h until a homogeneous solution is formed;
[0058] 2) Stir the above solution in a water bath at 80 °C for 3 h to evaporate the water, forming a wet gel. Subsequently, place the gel in an oven and dry it at 110 °C for 6 h to completely remove the water, and then grind it into powder;
[0059] 3) Place the above powder in a muffle furnace and heat it at a heating rate of 5 °C / min -1 to 450 °C and calcine it for 5 h to obtain an intermediate product, and then grind it into powder;
[0060] 4) Place the above powder in a muffle furnace and heat it at a heating rate of 5 °C / min -1 to 900 °C and calcine it for 12 h to obtain the cathode material Na 0.82 Li 0.1 Ni 0.24 Mn 0.66 O 2 .
[0061] Assemble the cathode material prepared in Comparative Example 1 into a CR2032 button battery according to the method in Example 1. At a current density of 0.1C, its initial discharge capacity is 161.2 mAh g -1 , and after 50 cycles, the capacity retention rate is 78.5%.
[0062] The above is only the specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art within the technical scope disclosed by the present invention can easily think of changes or substitutions, which should be covered within the protection scope of the present invention. Therefore, the protection scope of the present invention should be subject to the protection scope of the claimed rights.
Claims
1. A silicon-doped nickel-manganese-based layered oxide positive electrode material, characterized in that: Its chemical formula is Na x Li 0.1 Ni y Mn (1-0.1-y) Si z O2; wherein, 0.55≤x≤0.85, 0.1≤y≤0.4, 0<z<0.
1.
2. The method for preparing the silicon-doped nickel-manganese-based layered oxide positive electrode material according to claim 1, characterized in that: The following steps are involved: 1) preparing a citric acid aqueous solution, wherein the citric acid is used as a complexing agent; adding a lithium source, a transition metal element nickel source, a manganese source and a doping element silicon source thereto, and then adding a sodium source, and stirring to form a uniform solution; 2) heating and stirring the solution in step 1) in a water bath until a wet gel is formed, then drying the gel in an oven until the water is completely removed, and then grinding the obtained solid into powder; 3) placing the powder obtained in step 2) in a muffle furnace and calcining it at high temperature to obtain an intermediate product, and grinding the intermediate product into powder; 4) placing the powder in step 3) in a muffle furnace and performing secondary high-temperature calcination to obtain a positive electrode material Na2 doped with a P2 phase. x Li 0.1 Ni y Mn (1-0.1-y) Si z O2.
3. The method for preparing the silicon-doped nickel-manganese-based layered oxide positive electrode material according to claim 2, characterized in that: In the step 1), the stoichiometric ratio of citric acid to transition metal salt is between 1.5:1 and 2.5:1, and the transition metal salt is nickel salt and manganese salt; the amount of lithium source and sodium source added is 3-6% in excess by molar ratio.
4. The method for preparing the silicon-doped nickel-manganese-based layered oxide positive electrode material according to claim 3, characterized in that: The sodium source is any one of sodium acetate, sodium nitrate, sodium carbonate, and sodium bicarbonate; the lithium source is any one of lithium acetate, lithium nitrate, and lithium sulfate; the nickel source is any one of nickel acetate, nickel nitrate, and nickel sulfate; the manganese source is any one of manganese acetate, manganese nitrate, and manganese sulfate; and the silicon source is tetraethyl silicate.
5. The method for preparing the silicon-doped nickel-manganese-based layered oxide positive electrode material according to claim 2, characterized in that: In the step 2), the water bath temperature is 70-90° C.; the drying temperature is 105-125° C., and the drying time is 5-10 hours.
6. The method for preparing the silicon-doped nickel-manganese-based layered oxide positive electrode material according to claim 2, characterized in that: In step 3), the primary calcination temperature is 350-550°C, and the heating rate is 4-6°C min -1 The calcination time is 4-6h, followed by natural cooling.
7. The method for preparing the silicon-doped nickel-manganese-based layered oxide positive electrode material according to claim 2, characterized in that: In step 4), the secondary calcination temperature is 750-950°C, and the heating rate is 4-6°C min -1 The calcination time is 10-15h, followed by 4-6℃ min -1 Cool down to 400℃ and then cool naturally.
8. Use of the silicon-doped nickel-manganese layered oxide positive electrode material according to claim 1 in sodium ion batteries.
9. The use according to claim 8, characterized in that: Including Na x Li 0.1 Ni y Mn (1-0.1-y) Si z The positive electrode sheet made of a mixture of O2 powder, acetylene black and binder polyvinylidene fluoride is used as the positive electrode of the sodium ion battery, metallic sodium is used as the counter electrode, 5 vol% fluoroethylene carbonate is added to the NaClO4 / propylene carbonate with a concentration of 1 mol / L as the electrolyte, and glass fiber is used as the diaphragm. It is assembled into a CR2032 button battery in a high-purity argon atmosphere glove box with water and oxygen contents less than 0.01 ppm.